Problematika Sistem Proporsional Terbuka Pada Pemilihan Dewan Perwakilan Rakyat Republik Indonesia (Studi Putusan Mahkamah Konstitusi Nomor 114/PUU-XX/2022) - Rosmini; Paisal Abdi; IhsanTajali Nur (CV Putra Publisher, 2024)
The open proportional system used in the Election of the People's Representative Council of the Republic of Indonesia has been the subject of various controversies and debates. This study aims to analyze the problems arising from the implementation of this system, with a focus on the Constitutional Court Decision Number 114/PUU-XX/2022. This research uses a juridical-normative approach, reviewing statutory regulations, court decisions and relevant literature. The research results show that an open proportional system provides greater opportunities for voters to choose candidates directly, but also raises various problems, such as increasing campaign costs, increasingly sharp internal party competition, and the potential for money politics. Constitutional Court Decision Number 114/PUU-XX/2022 provides important legal views regarding the constitutional aspects of this system, but does not fully address the existing problems. This research concludes that although open proportional systems have advantages in increasing political representation and voter participation, further reforms are needed to overcome the problems that arise. The recommendations put forward include strengthening campaign regulations, increasing supervision of money politics, and improving internal party mechanisms to reduce friction. In this way, the electoral system can run more effectively and reflect people's aspirations more accurately.